THE EFFECT OF INNER DIAPHRAGMS AND NON-CONTINUOUS SILL SECTION ON THE STIFFNESS OF AUTOMOTIVE B-PILLAR - C.F. Tan; S.A. Shamsuddin; M.H. Shafie (Universitas Gadjah Mada, 2008)
The paper discusses the knowledge on the behaviour of T-frame under specific loading will be obtained by experimental methods in order to investigate the deflection of the vehicle B-pillar or T-frame. In addition, a series of T-frame were designed with inner diaphragm at various location in the sill member in order to investigate the effect of inner diaphragm and noncontinuous closed hat section in the sill member. Lastly, the results from the experimental tests were compared with the finite element analysis results to demonstrate the effectiveness of the inner diaphragm in the automotive B-pillar.